Electrostatic interaction map reveals a new binding position for tropomyosin on F-actin - Rynkiewicz, Michael; Schott, Veronika; Orzechowski, Marek; Lehman, William; Fischer, Stefan (Journal of muscle research and cell motility, 2015)
Azimuthal movement of tropomyosin around the F-actin thin filament is responsible for muscle activation and relaxation. Recently a model of αα-tropomyosin, derived from molecular-mechanics and electron microscopy of different contractile states, showed that tropomyosin is rather stiff and pre-bent to present one specific face to F-actin during azimuthal transitions. However, a new model based on cryo-EM of troponin- and myosin-free filaments proposes that the interacting-face of tropomyosin can differ significantly from that in the original model. Because resolution was insufficient to assign tropomyosin side-chains, the interacting-face could not be unambiguously determined. Here, we use structural analysis and energy landscapes to further examine the proposed models. The observed bend in seven crystal structures of tropomyosin is much closer in direction and extent to the original model than to the new model. Additionally, we computed the interaction map for repositioning tropomyosin over the F-actin surface, but now extended over a much larger surface than previously (using the original interacting-face). This map shows two energy minima—one corresponding to the “blocked-state” as in the original model, and the other related by a simple 24 Å translation of tropomyosin parallel to the F-actin axis. The tropomyosin-actin complex defined by the second minimum fits perfectly into the recent cryo-EM density, without requiring any change in the interacting-face. Together, these data suggest that movement of tropomyosin between regulatory states does not require interacting-face rotation. Further, they imply that thin filament assembly may involve an interplay between initially seeded tropomyosin molecules growing from distinct binding-site regions on actin.